The effect of Tabata-style functional high-intensity interval training on cardiometabolic health and physical activity in female university students - Lu, Yining; Wiltshire, Huw D.; Baker, Julien Steven; Wang, Qiaojun; Ying, Shanshan (Frontiers in Physiology, 2023)
High-intensity interval training (HIIT) improved cardiometabolic health in clinical adults but the evidence in the university setting is limited. Furthermore, few studies examined the effect of low-volume HIIT on habitual physical activity (PA). Therefore, the primary aim of this study was to evaluate the efficacy of a 12-week Tabata-style functional HIIT for improving cardiometabolic health and habitual PA. We also investigated whether changes in habitual PA over the intervention period had an impact on exercise-induced effects on health outcomes. 122 female freshmen (20.38±1.35 years old) were randomized into the Tabata group (n=60) and the control (n=62). The Tabata training protocol involved 8 x 20 s maximal repeated functional exercises followed by 10 s rest with a frequency of 3 times per week for 12 weeks. Body composition, maximal oxygen uptake (VO2max), blood pressure, blood lipids, fasting glucose and insulin, C-reactive protein and physical activity were objectively measured using standardized methods. Dietary intake was measured using a valid food frequency questionnaire. All variables were measured pre and post intervention. Following the intervention, compared to the control, the Tabata group experienced significant improvements in VO2max (12.87±7.16%), body composition (percentage body fat (-2.58±5.70%), fat mass (-2.61±6.72%), fat-free mass (1.07±2.69%), metabolic basal rate (0.95±2.36%), resting heart rate (-8.62±6.61%), some cardiometabolic health outcomes (systolic blood pressure (-3.66±4.12%), high-density lipoprotein (HDL) (8.55±10.44%), low-density lipoprotein (-1.95±6.05%), triglyceride (-1.08±6.81%), total-cholesterol (-1.07±3.60%), fasting insulin (-0.83±3.82%) and HOMA-IR (-1.6±4.70%)) and habitual PA (moderate-to-vigorous intensity physical activity (MVPA) (15.51±8.57%) and total physical activity (TPA) (14.92±9.93%)). Although the intervention had no significant training effect on weight, body mass index, or waist circumference, significant between-group differences were observed. Diastolic blood pressure, fasting glucose, HbA1c and C-reactive protein did not change significantly in both groups with no interaction effect. Regression analysis showed that only the percentage change of HDL was associated with the change of MVPA (b=0.326, p=0.015) and TPA (b=0.480, p=0.001). Conclusively, the 12-week Tabata-style functional HIIT was highly effective in improving cardiorespiratory fitness, body fat and some cardiometabolic health outcomes. Despite the absence of improvements in weight related variables, the health benefits of preventing abnormal weight gain in female freshmen was warranted.